Challenging exile: Japanese Canadians and the wartime constitution - Adams, Eric M. (Law and society series, 2025)
"In September 1945, Canada proposed exiling Japanese Canadians to Japan, a country devastated by war. Thousands who had experienced internment and dispossession were now at risk of banishment. In Challenging Exile, Eric M. Adams and Jordan Stanger-Ross detail the circumstances and personalities behind the exile. They follow the lives of families facing government orders that uprooted them from their homes, stripped them of their livelihoods and possessions, and proposed to exile them from Canada. And they analyze the court case in which lawyers and judges grappled with the meaning of citizenship, race, and rights in times of war and its aftermath. Unfolding in a context of global conflict, sharpened borders, and racist suspicion, the story told in Challenging Exile has enduring relevance for our own troubled times."--Page 4 of cover.